2017
DOI: 10.1038/s41598-017-14523-5
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Model of the Retinoic Acid Induced HL-60 Differentiation Program

Abstract: In this study, we present an effective model All-Trans Retinoic Acid (ATRA)-induced differentiation of HL-60 cells. The model describes reinforcing feedback between an ATRA-inducible signalsome complex involving many proteins including Vav1, a guanine nucleotide exchange factor, and the activation of the mitogen activated protein kinase (MAPK) cascade. We decomposed the effective model into three modules; a signal initiation module that sensed and transformed an ATRA signal into program activation signals; a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 120 publications
2
33
0
Order By: Relevance
“…In malignant promyelocytes, Vav1 interacts with both cytoplasmic and nuclear signaling molecules and participates in interconnected networks regulating the different aspects of ATRA-induced differentiation of APL-derived cells [29]. ATRA drives Vav1 expression and increases association of Vav1 and c-Raf, putatively promoting sustained MAPK pathway activation, cell cycle arrest and differentiation [30]. Vav has been found to be needed for myelopoiesis in knockout mice [31,32].…”
Section: Research Papermentioning
confidence: 99%
“…In malignant promyelocytes, Vav1 interacts with both cytoplasmic and nuclear signaling molecules and participates in interconnected networks regulating the different aspects of ATRA-induced differentiation of APL-derived cells [29]. ATRA drives Vav1 expression and increases association of Vav1 and c-Raf, putatively promoting sustained MAPK pathway activation, cell cycle arrest and differentiation [30]. Vav has been found to be needed for myelopoiesis in knockout mice [31,32].…”
Section: Research Papermentioning
confidence: 99%
“…Bistability is a common phenomena of cellular function, which is involved in many biological systems such as cell cycle progression [5][6][7], cell differentiation [11,29], as well as the development of cancer [13,24]. Although we do not consider the bistability, which originates from the positive feedback loops, in our model, the results in [5] show that the bistable steady states may accelerate the spatial activation of Cdks in Xenopus cell cycle.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…Retinoid X Receptor/Retinoic Acid Receptors are a group of nuclear receptors that form heterodimers upon All Trans Retinoic Acid (ATRA) or ligand binding. When ATRA binds, the pathway elicits a response that leads to the transcription of various genes through the activation of RAF/MAPK pathways [38,39]. We examined iPS87 cells for the presence of RXRα, one of the heterodimers of the complete complex.…”
Section: Retinoic Acid Receptor and Possible Differentiation Treatmentmentioning
confidence: 99%
“…Today, ATRA is clinically used for the treatment of psoriasis and Acute Myelocytic Leukemia (AML). Studies have shown that even at low concentrations of ATRA, binding to the Retinoic Acid or Retinoid Receptors leads to the differentiation or cell cycle arrest of the HL-60 cell line within 48 hours [38,40]. With the presence of RXRα in the iPS87 cell line, we were interested to examine the effects of ATRA treatment.…”
Section: Retinoic Acid Receptor and Possible Differentiation Treatmentmentioning
confidence: 99%